2020
DOI: 10.3390/ijms21041285
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic Insights of Calmodulin Gating of Complete Ion Channels

Abstract: Intracellular calcium is essential for many physiological processes, from neuronal signaling and exocytosis to muscle contraction and bone formation. Ca2+ signaling from the extracellular medium depends both on membrane potential, especially controlled by ion channels selective to K+, and direct permeation of this cation through specialized channels. Calmodulin (CaM), through direct binding to these proteins, participates in setting the membrane potential and the overall permeability to Ca2+. Over the past yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 128 publications
0
11
0
2
Order By: Relevance
“…In addition to these data, calmodulin was found significantly expressed in black soldier fly larvae with R. rhodochrous supplementation. Calmodulin binds calcium and has been implicated in inflammation, metabolism, and smooth muscle contraction (Nunez et al, 2020). Calcium is also required in many cases for initiation of DNA synthesis (Martelly et al, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these data, calmodulin was found significantly expressed in black soldier fly larvae with R. rhodochrous supplementation. Calmodulin binds calcium and has been implicated in inflammation, metabolism, and smooth muscle contraction (Nunez et al, 2020). Calcium is also required in many cases for initiation of DNA synthesis (Martelly et al, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…In the anhydrobiotic tardigrade, Hypsibius dujardini, a calmodulin inhibitor (J-8) and a calcium release modulator (2-APB) reduced the survival rate after rehydration, but the inhibitors against CaN and CaMK had no effect on the anhydrobiotic ability. Given that calmodulin regulates the gating of calcium ion channel in endoplasmic reticulum and mitochondrion as well as the signaling pathways 69,70 , the J-8 and 2-APB treatments may disrupt calcium storage in the organelles rather than calcium signalings, leading to malfunction of those intracellular organelles 71,72 . RNAi-based screening using the nematode Panagrolaimus superbus, showed that knockdown of “CAMK/CAMKL/MELK protein kinase” decreased the survival rate after rehydration 68 , whereas the contribution of CaN - NFAT pathway or CREB on the anhydrobiotic ability was not assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Tetrameroaren estruktura osoa ikusita, trukaturiko tentsioa detektatzeko eremua duela nabaritzen da. Hau da, tentsioa detektatzeko eremuaren ondoan, alboko azpiunitatearen poro-domeinua dauka (2. irudia [35][36][37]).…”
Section: Irudia K V 7 Kanalaren Estruktura (A) K V 7 Modeloaren Aurre...unclassified